# Documentation

### This is machine translation

Translated by
Mouseover text to see original. Click the button below to return to the English verison of the page.

# poly2rc

Convert prediction filter polynomial to reflection coefficients

## Syntax

k = poly2rc(a)
[k,r0] = poly2rc(a,efinal)

## Description

k = poly2rc(a) converts the prediction filter polynomial a to the reflection coefficients of the corresponding lattice structure. a can be real or complex, and a(1) cannot be 0. If a(1) is not equal to 1, poly2rc normalizes the prediction filter polynomial by a(1). k is a row vector of size length(a)-1.

[k,r0] = poly2rc(a,efinal) returns the zero-lag autocorrelation, r0, based on the final prediction error, efinal.

## Examples

collapse all

Given a prediction filter polynomial, a, and a final prediction error, efinal, determine the reflection coefficients of the corresponding lattice structure and the zero-lag autocorrelation.

a = [1.0000 0.6149 0.9899 0.0000 0.0031 -0.0082];
efinal = 0.2;
[k,r0] = poly2rc(a,efinal)
k =

0.3090
0.9801
0.0031
0.0081
-0.0082

r0 = 5.6032

## Limitations

If abs(k(i)) == 1 for any i, finding the reflection coefficients is an ill-conditioned problem. poly2rc returns some NaNs and provides a warning message in those cases.

## Tips

A simple, fast way to check if a has all of its roots inside the unit circle is to check if each of the elements of k has magnitude less than 1.

stable = all(abs(poly2rc(a))<1)

## Algorithms

poly2rc implements this recursive relationship:

$\begin{array}{c}k\left(n\right)={a}_{n}\left(n\right)\\ {a}_{n-1}\left(m\right)=\frac{{a}_{n}\left(m\right)-k\left(n\right){a}_{n}\left(n-m\right)}{1-k{\left(n\right)}^{2}},\text{ }m=1,2,\cdots ,n-1\end{array}$

This relationship is based on Levinson’s recursion [1]. To implement it, poly2rc loops through a in reverse order after discarding its first element. For each loop iteration i, the function:

1. Sets k(i) equal to a(i)

2. Applies the second relationship above to elements 1 through i of the vector a.

a = (a-k(i)*fliplr(a))/(1-k(i)^2);

## References

[1] Kay, Steven M. Modern Spectral Estimation. Englewood Cliffs, NJ: Prentice-Hall, 1988.